Seksisme Bahasa Pada Novel “Perempuan Di Titik Nol” Karya Nawal El-Saadawi Perspektif Gender: Penelitian - Evi Susiana T; Andi Srimularahma; Irna fitiana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the expression of language sexism contained in the novel Perempuan di Titik Nol by Nawal El-Saadawi using a gender perspective. The research method used in this study is descriptive qualitative, with library techniques and reading techniques used in analyzing and classifying data in the form of words, phrases, expressions, sentences containing language sexism in the novel Perempuan di Titik Nol with various forms of gender injustice, including; marginalization, subordination, stereotypes, violence, and workload. The results of the study indicate that there is sexist language in the novel Perempuan di Titik Nol by Nawal El-Saadawi with a total of 53 data. Namely marginalization there are 3 data that describe the marginalization and impoverishment of women, subordination there are 16 data that explain the exclusion of rights, secondary, demeaning, and neglect, stereotypes with 4 data telling about women who are given negative labels, violence with 24 data most describing women becoming victims of physical violence, physical and verbal harassment, and intimidation, and finally workload there are 6 data that explain the excessive burden received by women.